2010
DOI: 10.1016/j.joen.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Putative Stem Cells in Human Dental Pulp with Irreversible Pulpitis: An Exploratory Study

Abstract: Introduction-Although human dental pulp stem cells isolated from healthy teeth have been extensively characterized, it is unknown whether stem cells also exist in clinically compromised teeth with irreversible pulpitis. Here we explored whether cells retrieved from clinically compromised dental pulp have stem cell-like properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 31 publications
6
72
4
1
Order By: Relevance
“…Recent studies have reported the presence of viable stem cells in inflamed human dental pulps (Alongi et al 2010;Wang et al 2010;Pereira et al 2012). Our study also demonstrated that DPSCs isolated from teeth that were clinically diagnosed as IP preserved similar stem cell properties as DPSCs derived from healthy pulp, including morphology, colony-forming ; C, D) were seeded in the upper chamber.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Recent studies have reported the presence of viable stem cells in inflamed human dental pulps (Alongi et al 2010;Wang et al 2010;Pereira et al 2012). Our study also demonstrated that DPSCs isolated from teeth that were clinically diagnosed as IP preserved similar stem cell properties as DPSCs derived from healthy pulp, including morphology, colony-forming ; C, D) were seeded in the upper chamber.…”
Section: Discussionsupporting
confidence: 75%
“…This ablative approach is based on the generally accepted belief that once infection reaches the pulp, the infected and locally inflamed neurovascular structure may be irreversibly damaged with limited capability for repair. Recent studies reported that a subset of MSCs derived from inflamed human pulps preserve the full capability of proliferation and multipotent differentiation as compared with those from healthy pulps (DPSCs; Alongi et al 2010;Wang et al 2010;Pereira et al 2012), suggesting that inflamed pulp may not be completely depleted of progenitor/stem cells but can be repaired.…”
Section: Introductionmentioning
confidence: 99%
“…But MTA in its freshly mixed state shows a higher cytotoxicity [11,12] which could be due to its high pH [13]. Therefore, it is important to develop a new biocompatible material directed at maintaining a pulp vitality and increasing tooth longevity (Wang et al 2010) [14]. One such biologically based therapeutic is PRF.…”
Section: Discussionmentioning
confidence: 99%
“…In current case the molar tooth exhibited signs and symptoms that of irreversible pulpitis, probably the coronal pulp, near minute carious lesion exposure site, was irreversibly inflamed and the radicular pulp remained vital with reversible pulpitis, however, the accurate histological diagnosis will remain uncertain for the case. Diseased pulp may not be completely damaged and some of the pulp cell might have capacity as stem cell potential, similar to healthy cells for autologous regeneration of pulp tissue [28].…”
Section: International Journal Of Dental Sciences and Researchmentioning
confidence: 99%